The potential of multiprofessional collaboration in integrating dance in early additional language education in primary school - Korpinen Kaisa; Anttila Eeva (NTNU Open Access Journals, 2025)
This article explores how a multiprofessional team collaborates in integrating dance in early language education. It is based on the team members’ experiences and reflections as they combined dance with the teaching of Swedish as an additional language in grade 1 in a Finnish primary school. The project was framed by the notion of embodied learning understood as the holistic engagement of learners within their socio-material surroundings. Following socio-material approaches to education, the study examines the team of a dance teacher, a researcher, and the school’s class teachers as an assemblage and multiprofessional collaboration as events that cross subject boundaries. The data assemblage encompasses audio-recorded, embodied, and material documentation of weekly meetings, in which the team co-designed the activities. The analysis maps the collaborative process of integrating language and dance through the post-qualitative approach of embodied writing. It highlights the designed practices, the challenges and the possibilities of the collaboration, and the conditions for successful collaboration. Co-designing dance and language integrated pedagogy occurred in events of disciplinary crossings and in entanglement with the process of becoming an assembled team. These insights illuminate multiprofessional collaboration as an entry point to embodied and cross-disciplinary pedagogies in early language education in primary school.